Gallbladder Volvulus in a Patient with Type I Choledochal Cyst: A Case Report and Review of the Literature. (22nd September 2016) - Younan, George; Schumm, Max; Ali, Fadwa; Christians, Kathleen K.
Abstract : Introduction. Gallbladder volvulus is a rare, potentially fatal condition unless diagnosed and treated early. Choledochal cysts are rare congenital malformations of the biliary tree predisposing to different pathologies and posing the risk of degradation into cholangiocarcinoma and gallbladder cancer. Dealing with both diseases at once has not been published yet in the literature. Presentation of Case. We report a case of gallbladder volvulus in an elderly female who happened to have a concomitant type I choledochal cyst. Treatment was achieved with a cholecystectomy and observation and follow-up of the choledochal cyst. Discussion. Prompt diagnosis and surgical management of gallbladder volvulus is important to avoid the morbidity and mortality of gangrenous cholecystitis and biliary peritonitis in a frail old population of patients. Precise clinical diagnosis, supplemented with specific imaging clues, helps in the diagnosis. Management of choledochal cysts is also surgical; however the timing of surgery is still a matter of debate. Conclusion. We describe in this report the first case of gallbladder volvulus in a patient with a choledochal cyst and propose a management algorithm of a very rare biliary tree pathology combination.